2016
DOI: 10.1002/2016jd025042
|View full text |Cite
|
Sign up to set email alerts
|

ATMS‐ and AMSU‐A‐derived hurricane warm core structures using a modified retrieval algorithm

Abstract: The Advanced Technology Microwave Sounder (ATMS) is a cross‐track microwave radiometer. Its temperature sounding channels 5–15 can provide measurements of thermal radiation emitted from different layers of the atmosphere. In this study, a traditional Advanced Microwave Sounding Unit‐A (AMSU‐A) temperature retrieval algorithm is modified to remove the scan biases in the temperature retrieval and to include only those ATMS sounding channels that are correlated with the atmospheric temperatures on the pressure le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 26 publications
(32 reference statements)
0
27
0
Order By: Relevance
“…Temperature anomalies are traditionally computed with respect to a reference profile. Previous observational studies (e.g., Durden, ; Gao, Chen, et al, ; Komaromi & Doyle, ; Stern & Zhang, ; Tian & Zou, ; Wang et al, ; Zawislak et al, ; Zhu & Weng, ) used either the Dunion () moist tropical climatological sounding or the mean environmental sounding in an annulus. Several studies (e.g., Durden, ; Stern & Nolan, ; Stern & Zhang, ) showed that environmental soundings were generally warmer than the Dunion () sounding, especially at higher altitudes, which resulted in larger upper‐level anomalies and possibly greater maximum anomaly heights when using the Dunion () sounding.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Temperature anomalies are traditionally computed with respect to a reference profile. Previous observational studies (e.g., Durden, ; Gao, Chen, et al, ; Komaromi & Doyle, ; Stern & Zhang, ; Tian & Zou, ; Wang et al, ; Zawislak et al, ; Zhu & Weng, ) used either the Dunion () moist tropical climatological sounding or the mean environmental sounding in an annulus. Several studies (e.g., Durden, ; Stern & Nolan, ; Stern & Zhang, ) showed that environmental soundings were generally warmer than the Dunion () sounding, especially at higher altitudes, which resulted in larger upper‐level anomalies and possibly greater maximum anomaly heights when using the Dunion () sounding.…”
Section: Methodsmentioning
confidence: 99%
“…However, these AMSU‐A or ATMS‐derived warm‐core structures (Kidder et al, ; Tian & Zou, ; Weng et al, ; Zhu & Weng, ) were not verified by in situ dropsonde observations. Several previous studies have claimed that upper‐tropospheric warm cores in reanalyses (Hatsushika et al, ; Onogi et al, ) and AMSU‐A (Kidder et al, ) were consistent with the dropsonde observations of Hurricane Hilda (1964; Hawkins & Rubsam, ).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The algorithm developed by Zhu et al () was applied to ATMS observations of Hurricane Sandy (2012) and a positive correlation between the maximum upper level warm anomaly and the maximum sustained winds was found (Zhu and Weng (). Due to scan biases found in the temperature retrievals obtained by the algorithm of Zhu et al () and Zhu and Weng (), Tian and Zou () proposed four modifications to the temperature retrieval algorithm: (i) replace the simple scan correction term with regression coefficients that are explicit functions of scan position; (ii) use only a subset of ATMS temperature‐sounding channels for retrieving the temperatures at certain pressure levels that are highly correlated (correlation coefficients greater than 0.5) to these channels; (iii) obtain regression coefficients using limb‐corrected ATMS and collocated Global Positioning System (GPS) radio occultation (RO) observations in the month prior to the lifetime of the hurricane as training data sets; and (iv) obtain two sets of regression coefficients, one for clear‐sky conditions and another for cloudy‐sky conditions. The refined algorithm was applied to both AMSU‐A and ATMS observations to demonstrate that the warm‐core structures for Hurricanes Michael (2012) and Sandy (2012) during their lifetimes were more realistic than those obtained by both the unmodified algorithm and the even more advanced one‐dimensional variational approach of the Microwave Integrated Retrieval System.…”
Section: Introductionmentioning
confidence: 99%
“…The refined algorithm was applied to both AMSU‐A and ATMS observations to demonstrate that the warm‐core structures for Hurricanes Michael (2012) and Sandy (2012) during their lifetimes were more realistic than those obtained by both the unmodified algorithm and the even more advanced one‐dimensional variational approach of the Microwave Integrated Retrieval System. Tian and Zou () applied the temperature retrieval algorithm in Tian and Zou () to microwave temperature sounders onboard four NOAA operational satellites to analyze the intensity variations in Hurricanes Harvey, Irma, and Maria (2017).…”
Section: Introductionmentioning
confidence: 99%